PELATIHAN DIGITALISASI PENCATATAN BERBASIS APLIKASI KASIR PINTAR PADA UMKM BUBUR AYAM DI WILAYAH LENTENG AGUNG JAKARTA SELATAN - Asih Kustiah; Muhammad Fatih Setiaji; Ratna Fia Agustina; Ugik Setia Bekti; Zara Tania Rahmadi; Indra Setiawan; Kampono Imam Yulianto (ASOSIASI IDEBAHASA KEPRI, 2026)
Digital transformation is becoming a pressing necessity for micro-scale culinary businesses to stay competitive and transparent financially. As reported by Kemenkop UKM, “25,5 juta UMKM telah bertransformasi dan masuk ke dalam ekosistem digital” (Deputi Kewirausahaan, Siti Azizah). Meanwhile, government policy is strongly pushing this movement: “Targetnya 30 juta UMKM go digital pada 2024, sekarang ini sudah 27 juta,” said Rudy Salahuddin, Deputy for Digital Economy Coordination. This study investigates the effect of training bubur ayam (chicken porridge) micro-vendors in Lenteng Agung Selatan, Jakarta, in using the Kasir Pintar application for financial record-keeping. Through a community engagement action research approach, including participatory observation, in-depth interviews, and hands-on mentoring over 6–8 weeks, the program was implemented. Initially, most vendors relied on manual bookkeeping that was error-prone, unstructured, and lacked real-time reporting. After the intervention, participants significantly improved in daily transaction recording, accuracy of sales logs, and ability to read simple financial statements. However, barriers such as limited digital literacy, insufficient hardware (smartphones and receipt printers), and initial resistance to new technology were identified. These findings align with broader national digitalization efforts. For instance, Bank Indonesia has emphasized in its Go-Digital strategy that “digitalization of UMKM is essential not only for payments but for production, e-financing, and market access.” The study demonstrates that Kasir Pintar–based training can boost efficiency, professionalism, and financial transparency in micro culinary businesses. To ensure sustainable adoption, continued mentoring and device support are strongly recommended.